Kształtowanie jakości finansów publicznych i metody jej pomiaru - Zioło, Magdalena (Establishing The Quality of Public Finance and its Assessment, 2009)
The article defines the quality of public finance (QPF) and identifies factors which have the significant impact on it. The components of QPF have also been considered. The author presents the main methods and indicators measuring the QPF and emphasizes the major problems in the assessment process
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 387-393